Tips for the science teacher : research-based strategies to help students learn - Hartman, Hope J.; Glasgow, Neal A. (Thousand Oaks : Corwin Press, 2002)
This book describes instructional strategies for science teachers based on educational, psychological, and social research findings and focuses on how these results can be applied to classroom settings. Chapters include: (1) "Instructional Strategies"; (2) "Developing Students' Scientific Thinking and Learning Skills"; (3) "Emotional Aspects of Science Learning"; (4) "Social Aspects of Science Classroom"; (5) "Using Technology in Science Teaching"; (6) "Informal Science Learning"; and (7) "Assessment in the Science Classroom." Each chapter presents a collection of teaching tips, concisely presented in a user-friendly format which includes: "THE TIP"; "What the Research Says"; "Classroom Applications"; "Precautions and Possible Pitfalls"; and "Bibliographies." An index is also included (YDS).
Include index.
Keywords: Educational Strategies; Educational Technology; Elementary Secondary Education